Enhanced client polling with multilevel pre-fetching algorithm for wireless networks - Ahmad, Nazrul Muhaimin; Tan, Kim Geok (Korea Information and Communications Society (KICS), 2007)
The implementation of client polling as a weak cache coherence mechanism has two major drawbacks: Firstly, the cache may return a stale copy if the object is changed in the origin server while the cached copy is considered valid. Secondly, the cache can invalidate at cached copy that is still valid in the server. Therefore, we propose a multilevel pre-fetching (MLP) in conjunction with the client polling to refine these drawbacks. MLP is introduced to improve the level of freshness among the cached objects. The simulation results presented in this paper show that the proposed MLP significantly minimizes the number of stale objects and reduces the invalidation messages sent out to the server, i.e., increase the cache HIT rate.